Increased osmotic sensitivity for antidiuretic response in chronic chagas' disease - Joel Paulo Russomano Veiga; Tatsuto Kimachi; Euclydes Custódio Lima Filho; Luiz Fernando Junqueira Jr (Revista da Sociedade Brasileira de Medicina Tropical, 1985)
The osmotic threshold for attaining the antidiuretic response to hypertonic saline infusion and Progressive dehydration was studied in 31 patients with the chronic form of Chagas' disease and 16 control patients. The chagasic patients exhibited enhanced osmoticsensitivity to the antidiuretic response. This was demonstrated by lower values of the increments in plasma osmolarity sufficient to induce a significant fall in water clearance, without alterations in the osmolar clearance or creatinine excretion. The time needed to attain the antidiuretic response was shorterfor chagasics in relation to normal subjects. The results suggest the existence of a disturbance in the fine control of osmoregulation in the chagasic patients. They are interpreted to be a consequence of the denervation in hypothalamic or extrahypothalamic areas that regulate the secretion of vasopressin in chronic Chagas' disease. O limiar de sensibilidade osmótíca para obtenção de resposta antídiurética foi avaliado em 31 pacientes com a forma crônica da moléstia de Chagas, através de infusão de salina hipertônica ou desidratação. Os resultados, quando comparados com os obtidos em 16 pacientes-controle, mostram uma sensibilidade osmótíca aumentada para os chagásicos, dados os menores valores do incremento na osmolaridade plasmática, suficiente para induzir uma queda significativa na depuração de água livre, sem alterações na depuração osmolar ou na excreção de creatínina. Também, o tempo necessário para atingir a antídiurese foi mais curto para os chagásicos do que para os controles. Os resultados sugerem a existência de um distúrbio na osmorregulação, nos pacientes chagásicos, caracterizado por uma sensibilidade osmótíca aumentada dos osmorreceptores para liberação da vasopressina. Estes dados interpretam-se como conseqüente à desnervação em áreas hipotalâmicas ou extra-hipotalâmicas, relacionadas com a secreção do hormônio antidiurético, na doença de Chagas.